Plato Baptized: Towards the Interpretation of Spenser's Mimetic Fictions - Bieman, Elizabeth (Heritage, 1988)
Bieman argues that from experiences of personal knowing the writer, his fictive protagonists, the reader and the interpreter participate in the production of further experiences throughout which other meanings may, evanescently, be glimpsed.